Application and research status of auricular acupoint pressing bean therapy in relieving insomnia in patients with type 2 diabetes mellitus (耳穴压豆在改善2型糖尿病伴失眠患者中的应用现状) - XIANG Yiming (向毅明); XIE Wei (谢薇); LIU Qing (刘青); DONG Huaqian (董画千); YUAN Dan (袁丹); ZHAO Lingling (赵玲玲); GAN Lu (甘露) (中西医结合护理)
With the increasing incidence of diabetes mellitus in China, the sleep problem of diabetic patients has become increasingly prominent, which greatly reduces the quality of life of patients, and has brought a great impact on the treatment and control of the disease. With the national attention to the traditional Chinese medicine therapy, auricular acupoint pressure bean therapy as one of the appropriate Traditional Chinese Medicine nursing techniques, in the improvement of diabetes sleep quality clinical effect has been widely concerned. This paper reviewed literatures on the effect of auricular acupoint pressing bean therapy on improving sleep quality, aiming to provide theoretical basis of TCM treatment for improving sleep quality of patients with type 2 diabetes. (近年来, 糖尿病患者的睡眠问题逐渐突显, 严重影响患者的生活质量, 给疾病的治疗与控制造成了很大的影响。耳穴压豆作为中医护理适宜技术之一, 在改善糖尿病患者睡眠质量的临床疗效方面得到了广泛关注。本文通过对耳穴压豆在改善睡眠质量上的诸多文献进行综述, 旨在为改善2型糖尿病患者睡眠质量的护理提供中医治疗理论依据。)